The molecular epidemiology and diversity of gastroenteritis viruses in HIV-infected, -exposed and -unexposed children under the age of five years in Pretoria, South Africa - Mans, Janet (University of Pretoria, 2020)
Dissertation (MSc (Medical Virology))--University of Pretoria, 2020.